Recurrent Scedosporium apiospermum mycetoma successfully treated by surgical excision and voriconazole - Chi-Hsuan Chiang; Chao-Kai Hsu; Julia Yu-Yun Lee; Tsung Chain Chang; Yuan-Yu Hsueh; Shyh-Jou Shieh; Hung-Mo Chen; Mark Ming-Long Hsu (Wolters Kluwer Medknow Publications, 2014)
Scedosporium apiospermum is an emerging opportunistic fungus that can cause localized infection in healthy hosts or severe disseminated disease in immunocompromised hosts. Most cases are reported in Western Europe, Australia, and North America. We report a 52-year-old immunocompetent Taiwanese woman who presented with a 6-year history of recurrent asymptomatic papulonodular lesions on her right foot after minor trauma. Deep fungal infection caused by Scedosporium sp. was diagnosed after a skin biopsy with fungal culture of the skin specimen. She underwent two surgical excisions, each followed by a 4-month course of oral itraconazole and intralesional injections of amphotericin B as well, but similar lesions recurred at the same location 1 year later. She had another surgical excision and the pathological findings showed mycetoma. The fungus was identified as S. apiospermum by PCR assay of fungal culture specimen using the internal transcriber spacers (ITS1, similarity 99.4%; ITS2, similarity 100%) and the D1-D2 (similarity 99.0%) regions of the ribosomal operon. After 4 months of oral voriconazole (400 mg/day), no recurrence was noted in the subsequent 2 years.